A novel Slide-seq based image processing software to identify gene expression at the single cell level - Götz, Theresa; Cong, X.; Rauber, Simon; Angeli, Mario Raphael; Lang, E. W.; Ramming, Alina; Schmidkonz, Christian (Journal of Pathology Informatics, 2024)
Analysis of gene expression at the single-cell level could help predict the effectiveness of therapies in the field of chronic inflammatory diseases such as arthritis. Here, we demonstrate an adopted approach for processing images from the Slide-seq method. Using a puck, which consists of about 50,000 DNA barcode beads, an RNA sequence of a cell is to be read. The pucks are repeatedly brought into contact with liquids and then recorded with a conventional epifluorescence microscope. The image analysis initially consists of stitching the partial images of a sequence recording, registering images from different sequences, and finally reading out the bases. The new method enables the use of an inexpensive epifluorescence microscope instead of a confocal microscope.
CRIS-Team Scopus Importer:2024-06-28
Keywords: Cell segmentation; Deep neural networks; DNN complexity; Pruning; Slide-seq